Impact of 2012 USPSTF Screening PSA Guideline Statement: Changes in Primary Care Provider Practice Patterns and Attitudes. Issue 2 (March 2017) - Miller, Alexander; Yates, Jennifer; Epstein, Mara M.; Fantasia, Jennifer; Frendl, Daniel; Afiadata, Achankeng; Sokoloff, Mitchell; Luckmann, Roger
ABSTRACT : Introduction: : Prostate specific antigen use in prostate cancer screening has undergone significant changes since the 2012 release of the USPSTF (United States Preventive Services Task Force) guideline statement. The effect on specific primary care provider practice patterns and attitudes is not well characterized. We describe the impact of the USPSTF statement on prostate cancer screening practices, attitudes and knowledge among primary care providers. Methods: : A survey composed of 25 questions was mailed electronically to approximately 350 primary care providers within a single academic health care system. Responses were recorded and could not be traced to the respondent. Results: : A total of 73 primary care providers (21%) responded to the survey. Of the respondents 75% reported a change in prostate specific antigen screening practices resulting from the USPSTF recommendations and 35% reported a decrease in digital rectal examination use, although the latter test is not explicitly addressed in the guideline statement. A third of respondents believe that prostate specific antigen screening has "likely had no role" in the 2‐decade decline in prostate cancer mortality and 70% agree that prostate specific antigen screening may "impart more harm than good" to the patient. Despite these opinions, there was markedly greater concern for medicolegal consequences of a missed diagnosis compared to over diagnosis. Conclusions: : The results of the survey, while limited to a single large academic center, show the impact of the USPSTF 2012 statement on physician attitudes and practice patterns. The results define the need for more educational opportunities for primary care providers regarding the USPSTF statement, American Urological Association guidelines and identification of patients appropriate for prostate specific antigen screening.